Aseptic Loosening of Total Hip Arthroplasty as a Result of Local Failure of Tissue Homeostasis - Gallo, Jiri; Konttinen, Yrjö T.; Goodman, Stuart B.; Thyssen, Jacob P.; Gibon, Emmanuel; Pajarinen, Jukka; Takakubo, Yuya; Schalock, Peter; Mackiewicz, Zygmunt; Jämsen, Eemeli; Petrek, Martin; Trebse, Rihard; et al. (IntechOpen, 2012)
None